Inducibility of aryl hydrocarbon hydroxylase in cultured human lymphocytes: a study of repeatability. - Fletcher, K A (1978)
Modifications to the method for estimating aryl hydrocarbon hydroxylase (AHH) activity in cultured human lymphocytes are described. Despite the improvements to the technique it was not possible to show significant 'repeatability' of values for AHH induction over a period of 2 weeks or more. Significant repeatability could be seen when a blood sample from each subject was split into duplicates. However, this level of repeatability was low when considered for quantitative genetics purposes. Possible reasons for the poor repeatability have been discussed.